The Role of the Aru Islands Regency Education and Culture Service in Addressing the Duties and Responsibilities of Teachers at Aru Island Christian Middle School 3 - Melanie Dee Miana Elsurun Vannon; Titus Gaite; Ridwan Hatala (CV. Rayyan Dwi Bharata, 2024)
This research aims to describe the role of the Aru Islands Regency Education and Culture Service in responding to the duties and responsibilities of teachers at Aru Island 3 Christian Middle School. This research method is a descriptive qualitative approach. Data collection techniques are observation, interviews and documentation. The results of this research show that the Aru Islands Regency Education and Culture Service has a role in providing education, therefore every existing problem must be paid attention to and considered fairly and evenly in each educational unit. The Department of Education and Culture plays a role in managing the budget to support education, of which 20% of the funding goes to non-physical matters such as salaries and allowances, while the remaining 10% is funding for office needs or funding for accompanying programs in educational development. Then the Department of Education and Culture plays the role of supervisor and supervisor in improving the discipline of teachers' duties and responsibilities. The Education Service has the right to obtain reports on teaching and learning activities, monitor supervision, recapitulate attendance, provide guidance for teachers who violate the rules. So the evaluation carried out by the Education and Culture Service regarding what was found then implemented Android-based attendance, then carried out joint control with the PP Unit, Village Head and Religious Leaders over teachers in the Village. From the role played by the Department of Education and Culture, there are several inhibiting factors for teachers in carrying out their duties and responsibilities, namely geographical location, sea transportation, natural conditions, limited teacher housing, salary income, and internet networks. The inhibiting factor that teachers face is adapting to existing circumstances, this variable can control behavior. This is supported by the Teacher Work Discipline Theory according to Hamza Uno and Nina Lamatenggo 2016. In examining the variable approach to work discipline according to Kelvin Seifert, there is a humanism approach (based on responsibility), a negotiation approach (intervention assistance), and a behavior modification approach (assessing cause and effect)